2021
DOI: 10.3390/ijms22116025
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of PGC-1α to Obesity- and Caloric Restriction-Related Physiological Changes in White Adipose Tissue

Abstract: Peroxisome proliferator-activated receptor γ coactivator-1 α (PGC-1α) regulates mitochondrial DNA replication and mitochondrial gene expression by interacting with several transcription factors. White adipose tissue (WAT) mainly comprises adipocytes that store triglycerides as an energy resource and secrete adipokines. The characteristics of WAT vary in response to systemic and chronic metabolic alterations, including obesity or caloric restriction. Despite a small amount of mitochondria in white adipocytes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 139 publications
0
30
0
1
Order By: Relevance
“…Phosphorylated AMP-activated protein kinase alpha (pAMPKα), which is a crucial factor for energy homeostasis in adipose tissue [ 46 ] inhibits adipocyte differentiation [ 47 ] and adipogenesis [ 48 , 49 ]. Moreover, pAMPKα interacts with PPAR-γ coactivator 1 alpha (PGC-1α), which suppresses adipogenesis via morphological changes in white adipose tissue [ 50 ]. In the present study, both WP supplementation itself demonstrated by PGC-1α and WP supplementation with RE represented by pAMPK/AMPK improved energy metabolism homeostasis in sarcopenic obesity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated AMP-activated protein kinase alpha (pAMPKα), which is a crucial factor for energy homeostasis in adipose tissue [ 46 ] inhibits adipocyte differentiation [ 47 ] and adipogenesis [ 48 , 49 ]. Moreover, pAMPKα interacts with PPAR-γ coactivator 1 alpha (PGC-1α), which suppresses adipogenesis via morphological changes in white adipose tissue [ 50 ]. In the present study, both WP supplementation itself demonstrated by PGC-1α and WP supplementation with RE represented by pAMPK/AMPK improved energy metabolism homeostasis in sarcopenic obesity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both WP supplementation itself demonstrated by PGC-1α and WP supplementation with RE represented by pAMPK/AMPK improved energy metabolism homeostasis in sarcopenic obesity [ 51 ]. It is expected that WP supplementation regardless of RE significantly reduced fat mass and fat (epididymal) weight by inhibiting adipocyte differentiation demonstrated by PPAR-γ and C/EBPα under the activation of PGC-1α and AMPK in sarcopenic obese condition [ 50 ]. Adipose tissue maintains energy homeostasis itself and that of other organs by secretion and communication [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected two hub genes (PPARGC1a and COQ3) that were downregulated in all datasets and were closely related to mitochondrial function. Downregulation of PPARGC1a impairs mitochondrial biogenesis and oxidative metabolism in obesity (46). PPARGC1a expression has been reported to be altered in neurodegenerative disorders, leading to mitochondrial defects and increased ROS levels; increasing its levels results in reductions in Alzheimer's disease pathology and improvements in behavior (47).…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction and exercise contribute to PGC1α activation and associated health outcomes [ 343 , 344 , 345 , 346 , 347 , 348 ]. Aligning meal times with the circadian rhythms by time-restricted feeding in animal models can also modulate PGC1α activity and mitochondrial biogenesis.…”
Section: Mechanisms Of Chrononutrition In Energy Homeostasis and Obesitymentioning
confidence: 99%